A AUTOAVALIAÇÃO INSTITUCIONAL NO ENSINO SUPERIOR: A PERSPECTIVA E ESTRATÉGIA DISCENTES - Alves, Marcelo Leandro Ferraz (2014)
The National System of Higher Education Assessment (SINAES) includes as one of its indicators, the Institutional Self-Assessment of responsibility for their own higher education institutions (HEIs) and promoted in its scope, the Standing Committees of rating (CPA). These evaluations should generate internal actions in HEIs in order to qualify their services, facilities and professionals. The evaluation fulfills functions that involve power relations and strategies developed by their users to achieve their goals. It is important, therefore, to identify those mechanisms that directly influence the completion of assessment tools and impacting the income earned and the actions resulting from this process. This study aims to examine what are the mechanisms, strategies and power relations involved in making the institutional assessment from the representations of the respondents including teachers and students. The objective is to analyze, through a qualitative research, self-assessment in higher education and institutional mechanisms present in its realization, seeking to identify the power relations and strategies developed from interviews of a sample of students and teachers participating process.